When a subclavian artery is equivalent to STEMI of left main coronary artery: a case report - Abdelrahman Elhakim; Mohamed Elhakim; Derk Frank; Mohammed Saad (BMC Cardiovascular Disorders)
Abstract An 81-year-old man with known ischemic heart disease and coronary artery bypass graft (CABG) was admitted with cardiogenic shock and ST segment elevation myocardial infarction (STEMI) of the anterior and lateral wall. Coronary angiography showed a total occlusion of left main coronary artery and acute thrombotic proximal segmental occlusion of the left subclavian artery before the origin of left internal mammary artery (LIMA). Successful percutaneous intervention proximal to the LIMA origin led to immediate restoration of antegrade flow in the left internal mammary artery (LIMA) to the left coronary circulation, stabilizing hemodynamics, and relieving symptoms.